The court metaphor is changing. New criminal theories and the Last Judgment Die Gerichtsmetapher im Wandel. Neue Straftheorien und das Jüngste Gericht - Teuchert, Lisanne (Evangelische Theologie, 2023)
This paper presents changing conceptions of the court scene as reflected in recent theories of punishment. These mainly concern the inclusion of emotions, the breaking of the fixation on the offender and the role of the public. Theology as well as criminal law are working to dismantle a horror image of the court. How the emergence of new images of horror can be prevented is the subject of the article with regard to the consequences for a theology of the Last Judgement.
CRIS-Team Scopus Importer:2024-09-30